Fluorine speciation and origin of Early-Middle Triassic bentonite deposits in Sichuan Basin, South China - Lin, Yongjie; Zheng, Mianping; Zhang, Yongsheng; Xing, Enyuan (Frontiers in Earth Science, 2023)
Fluorine (F) is one of the most important environmentally harmful elements released by volcanic activity, and the bentonite deposits that formed from volcanic ashes are potentially harmful to the environment. However, the mechanisms governing F-rich bentonite formation and its F speciation composition remain enigmatic. The F-rich bentonite deposits are widely distributed in the Early-Middle Strata of the Sichuan Basin, South China. Detailed mineralogical and geochemical studies were conducted on the bentonite deposits from five sections of the Sichuan Basin. X-ray diffraction (XRD) analyses indicate that the F-rich bentonites mainly contain quartz, carbonates (calcite and dolomite) or gypsum, and clay minerals, while the clay minerals are dominated by illite and illite/smectite (I/S). Clay mineralogical studies suggest that bentonites were transformed from volcanic ashes during diagenesis by smectite illitization. The major and trace element distribution in F-rich bentonite deposits altered from volcanic ashes is most likely derived from felsic magmas, and alteration of the parent rocks (e.g., rhyolites) to bentonite is associated with leaching and subsequent removal of F. The total fluorine content (FTOT) of the bentonite samples ranged from 1,162 mg/kg to 2,604 mg/kg (average = 1773 mg/kg), well above the average FTOT contents of soils in the world. The results of the sequential extraction experiments show that the highest content is residual-fluorine (Fres), followed by carbonate-fluorine (Fcar) with a mean value of 1,556 mg/kg and 186 mg/kg, indicating carbonate is an important F sink in bentonite deposits. The average fluorine value of organic fluorine (For), Fe/Mn oxide-fluorine (Ffm) and exchangeable fluorine (Fex) are relatively low with an average value of 17.5 mg/kg, 6.8 mg/kg and 4.1 mg/kg, respectively. However, water-soluble fluorine (Fws) has a mean value of 4.0 mg/kg, which is higher than the corresponding average value in soils in an area susceptible to endemic fluorosis in China. Based on the characteristic of fluorine speciation, the fluorine in bentonite deposits may pose a risk to the environment. This study makes an important contribution to a better understanding of the characteristic of fluorine speciation in bentonites and the formation mechanism that governs fluorine enrichment in bentonites.